Manufacturing processes for advanced composites - Campbell, F. C. (Flake C.) (Elsevier, 2004)
& bull; One of very few books available to cover this subject area. & bull; A practical book with a wealth of detail. This book covers the major manufacturing processes for polymer matrix composites with an emphasis on continuous fibre-reinforced composites. It covers the major fabrication processes in detail. Very few books cover the details of fabrication and assembly processes for composites. This book is intended for the engineer who wants to learn more about composite processing: any one with some experience in composites should be able to read it. The author, who has 34 years experience in the aerospace industry, has intentionally left out mathematical models for processes so the book will be readable by the general engineer. It differs from other books on composites manufacturing in focusing almost solely on manufacturing processes, while not attempting to cover materials, test methods, mechanical properties and other areas of composites.